The embassy of Sir Thomas Roe to the court of the Great Mogul, 1615-1619 : as narrated in his journal and correspondence.: as narrated in his journal and correspondence. Volumes I-II (2017) - Sir, Roe, Thomas, 1581?-1644
No abstract available